Pelatihan PSAK 109 Guna Membantu Pemahaman Mahasiswa Dalam Penerapan Akuntansi Zakat, Infaq dan Sedekah - Gusneli, Gusneli; Bakri, Asri Ady; Kalsum, Ummu; Zunaidi, Arif; Sholikah, Maratus; Putri, Firda Salsabila Sivana; Lestari, Novita Sri (Welfare : Jurnal Pengabdian Masyarakat, 2023)
This article discusses PSAK 109 training, which aims to help students understand the application of zakat, infaq, and alms accounting. This service activity was carried out on Tuesday, June 16, 2023, through an online session that involved several collaborator lecturers from various universities. The training materials include an introduction to the concepts of zakat, infaq, and alms and their implementation in PSAK 109. In addition, the basic principles of accounting and the recognition, measurement, and recording of zakat, infaq, and alms funds are also discussed in depth. Case studies, group discussions, and field simulations are applied to strengthen students' understanding and skills in managing religious funds with accountability and ethics. This training succeeded in providing significant benefits by integrating religious values with accounting practices in order to realize social and economic justice in society.